Analisis Pengaruh Retailing Mix Terhadap Volume Penjualan Pada Toko Ova Gedong Meneng Bandar Lampung - Muhammad Farid Naufal (Jurnal Manajemen dan Bisnis (JMB), 2020)
AbstractThis research aims to know the influence of product, price, location, personnel, promotion, and presentation against to volume of seles at OVA store Gedong Meneng Bandar Lampung. Analytical tools used in this research is to test the validity and test reability, classic assumption test that includes a test of normality test, and test heterokedasititas, and multikolinieritas test. The statistical tools used was multiple linier regression analysis and test of hypothesis which consists of test coeffient of determination (R2), the F test and t test. Dependent variables in the study is Sales Volume. Independent variables in the study is product, price, location, personnel, promotion, and presentation.this type of research is descriptive. The population in the research in the consumer OVA store Gedong Meneng Bandar Lampung with sampling tecniquies using purposive sampling technique with the total sample as many as 65 people. The result showed that the simultaneous product, price, location, personnel, promotion, and presentation together influential significantly to volume of sales. While partially product, location, promotion and presentation has no effect against a significant volume of sales. Meanwhile price, and personnel influential significantly to volume of sales.  Key Words : Retailing Mix, Sales Volume